The role of gasdermin-mediated mitochondrial RNA release in amplifying secondary immune response during microbial infection - Afaq, Uzair; Qudus, Muhammad Suhaib; Liu, Siyu; Wu, Kailang; Chen, Yu; Tian, Mingfu; Wu, Jianguo (Frontiers in Immunology, 2026)
Cytoplasmic RNA serves as a typical damage-associated molecular pattern (DAMP) signal; yet the mechanisms governing its release and role in inflammatory tissue damage remain poorly understood. In our study, we demonstrated that mimicking bacterial infection by lipopolysaccharide (LPS) combined with Nigericin (Ng) effectively activates Gasdermin D (GSDMD). Conversely, Vesicular Stomatitis Virus (VSV) selectively activates Gasdermin E (GSDME). Both GSDMD and GSDME form pores in the mitochondrial membrane, facilitating the release of mitochondrial RNA (mtRNA) into the cytosol. This released mtRNA is recognized by the RNA sensor Viral Interferon Stimulated Gene Activator (VISA), which subsequently induces a robust secondary inflammatory response. Importantly, the inhibition of GSDMD and GSDME prevents mitochondrial dysfunction and mtRNA release, thereby attenuating secondary inflammatory response mediated by the VISA pathway. Utilizing an experimental mice model, we found that LPS-induced lung tissue inflammation was restored by VISA knockout (VISA-/-) mice. Our findings highlight the potential targeting of GSDMD, GSDME, or VISA pathway signaling as a therapeutic strategy to modulate mtRNA-mediated inflammatory responses in microbial infectious diseases.